2022
DOI: 10.1136/bmjopen-2021-054919
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on acute trauma and orthopaedic referrals and surgery in the UK during the first wave of the pandemic: a multicentre observational study from the COVid Emergency-Related Trauma and orthopaedics (COVERT) Collaborative

Abstract: ObjectiveThis is the first British multicentre study observing the impact of the COVID-19 pandemic on orthopaedic trauma with respect to referrals, operative caseload and mortality during its peak.DesignA longitudinal, multicentre, retrospective, observational, cohort study was conducted during the peak 6 weeks of the first wave from 17 March 2020 compared with the same period in 2019.SettingHospitals from six major urban cities were recruited around the UK, including London.ParticipantsA total of 4840 clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…As most hospitals had to ensure sufficient capacity for the surge of COVID-19 patients, patients admitted during the COVID-19 pandemic period are likely a selection of more urgent and complex patients for which care could not be postponed. This is supported by findings of two previous studies reporting higher mortality for orthopaedic patients admitted during the COVID-19 pandemic when compared with the pre-pandemic period 14 21. Yet, other studies found similar mortality risks when examining the impact of the COVID-19 pandemic for hip fracture patients22 23 and patients who underwent hip or knee arthroplasty surgery24 compared with expected mortality risks based on pre-pandemic years.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…As most hospitals had to ensure sufficient capacity for the surge of COVID-19 patients, patients admitted during the COVID-19 pandemic period are likely a selection of more urgent and complex patients for which care could not be postponed. This is supported by findings of two previous studies reporting higher mortality for orthopaedic patients admitted during the COVID-19 pandemic when compared with the pre-pandemic period 14 21. Yet, other studies found similar mortality risks when examining the impact of the COVID-19 pandemic for hip fracture patients22 23 and patients who underwent hip or knee arthroplasty surgery24 compared with expected mortality risks based on pre-pandemic years.…”
Section: Introductionsupporting
confidence: 68%
“…COVID-19 caused by the SARS-CoV-2 virus had a tremendous effect on healthcare systems worldwide. Hospitals had to restructure to accommodate the influx of COVID-19 patients and prioritise acute care for non-COVID-19 patients, which disrupted orthopaedic care worldwide including reductions in elective and emergency surgical interventions,1–13 reduced clinic capacity3 4 6 10 12 and a decrease in orthopaedic trauma referrals and emergency admissions 6 7 12 14 15. Even more, the COVID-19 pandemic have led to an estimated total health loss for elective orthopaedic arthroplasty patients of approximately 30 000 QALYs, with decades of back-log of surgical capacity for these patients if capacity is not increased 13.…”
Section: Introductionmentioning
confidence: 99%
“…This notable drop could be the result of nationwide lockdowns which have occurred in the Kingdom of Saudi Arabia and across nations worldwide, along with the fear of attending the healthcare setting due to the risk of catching the infection. Similar drops have been witnessed across countries during the same period including the United Kingdom (UK) and Italy, increasing the likelihood of it being outbreak related [12][13][14] .…”
Section: Discussionmentioning
confidence: 57%
“…18 Sugand K et al in a longitudinal, multicenter, retrospective, observational, cohort study conducted in United Kingdom during the peak 6 weeks of the first wave from 17 March 2020 compared with the same period in 2019 observed, that for the patients undergoing surgery for acute orthopaedic trauma during COVID-19, there was an increase in odds of aerosolising-generating anaesthesia by three-quarters. 19 In summary, it is obvious that the emergency trauma surgeries will continue even during pandemics in periods of general lockdown as well as unlock. Anaesthesia teams working in centres with trauma care must consider this while developing strategies and reallocating resources during such health emergencies, epidemics or pandemics.…”
Section: Discussionmentioning
confidence: 99%